Water Quality Status Based on Pollution Index to Meet The Needs of Sanitary Hygienic Water For Communities Around Lake Sentani In Jayapura Regency - Bambang Suhartawan; Alfred B. Alfons; Daawia Daawia (Journal Research of Social Science, Economics, and Management, 2022)
Water is one of the most important elements on earth. Water is needed by all living things, both humans, plants and animals. Consuming clean and sanitary water is absolutely necessary to avoid unwanted negative impacts. This research was conducted in February 2022 and aims to determine the status of the water quality of Lake Sentani, Jayapura Regency based on the pollution index according to the hygienic and sanitary water quality standards according to the Regulation of the Minister of Health of the Republic of Indonesia Number: 32 of 2017 concerning Environmental health quality standards and water health requirements for sanitation hygiene needs, swimming pools, solus per agua and public baths. The study used 15 (fifteen) water pollution parameters, namely: physical parameters (turbidity, color, TDS and temperature), and chemical parameters (pH, iron, fluoride, hardness, manganese, nitrate, cyanide, detergent and total pesticides) as well as biological parameters. (total coliforms). The sample in this study was taken from 5 (five) sample points (research stations) namely the mouths of the Haway, Yabawi, Hobay and Kamwalker rivers which are the inlet of Lake Sentani and the headwaters of the Jaifuri river which is the outlet. The results showed that at stations 1, 2, 3, 4 and 5, the pollution index (PIj) was 4.07; 3.10; 2.30; 3.75 and 3.88, all of which are based on the Regulation of the Minister of Health of the Republic of Indonesia Number: 32 of 2017 especially environmental health quality standards and water health requirements for sanitation hygiene purposes, are in the range of values of 1 PIj 5 with lightly polluted status. Thus it can be concluded that the water quality status of Lake Sentani based on the pollution index method is in the lightly polluted category.